Functional brain response to food images in successful adolescent weight losers compared with normal‐weight and overweight controls. (3rd February 2015) - Jensen, Chad D.; Kirwan, C. Brock
<x xml:space="preserve">Abstract</x> Objective Research conducted with adults suggests that successful weight losers demonstrate greater activation in brain regions associated with executive control in response to viewing high‐energy foods. No previous studies have examined these associations in adolescents. Functional neuroimaging was used to assess brain response to food images among groups of overweight (OW), normal‐weight (NW), and successful weight‐losing (SWL) adolescents. Methods Eleven SWL, 12 NW, and 11 OW participants underwent functional magnetic resonance imaging while viewing images of high‐ and low‐energy foods. Results When viewing high‐energy food images, SWLs demonstrated greater activation in the dorsolateral prefrontal cortex (DLPFC) compared with OW and NW controls. Compared with NW and SWL groups, OW individuals demonstrated greater activation in the ventral striatum and anterior cingulate in response to food images. Conclusions Adolescent SWLs demonstrated greater neural activation in the DLPFC compared with OW/NW controls when viewing high‐energy food stimuli, which may indicate enhanced executive control. OW individuals' brain responses to food stimuli may indicate greater reward incentive processes than either SWL or NW groups.